Regional Innovation Model as an Acceleration Strategy Economic Growth in Blitar City - Tris Kamila Rosida; Farida Rahmawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Digital Economy has been established as a development strategy for Blitar City in 2021-2026 in the future. This is also supported by the desire to advance competitiveness in the economic sector as stated in the theme of the development of the City of Blitar in 2020, namely "Utilizing Regional Economic Competitiveness Supported by Human Resources Management and Apparatus". The determination of the development theme was motivated by development problems such as increasing poverty rates, increasing unemployment, income inequality (Blitar City Profile 2018, Bappeda). In addition, the local government of Blitar City is also faced with the problem of the lack of good governance due to the lack of integration among OPD (Regional Apparatus Organizations). Therefore, in dealing with these problems, the local government of Blitar City applies a strategy based on digital information to the people of Blitar City. In developing innovation, the local government of Blitar City designed an application that covers public services by providing information systems in the form of urban village services, population services, employment services, and licensing services. The development of this innovation is also a development strategy for the local government of Blitar City to realize a Smart City-based city.